As cotas raciais em uma publicação jornalística universitária: imagens das relações raciais brasileiras - Juliana Silva Santos (2016)
The goal of this research is to analyze the argumentative resources used in opinion articles published in Boletim, a weekly newspaper from Universidade Federal de Minas Gerais, in order to consider how the image of Affirmative Action was built, focusing on imaginaries underpinning the positions taken by speakers the writers of the opinion articles. The chosen texts were taken from the digital version of the aforementioned source and cover ten years of publication (2002 up to 2012). In this context, we point out that the proposal for such a measure which targeted the Black segment of the population, was created in a space of struggles and of polarized opinions regarding social relations, a situation that is materialized discursively. Thus, we assume that doxic elements such as stereotypes and socio-discursive imaginaries, beyond the arguments conveyed by the speech (ethos, pathos and logos) are used in the argumentative building of the speakers to support their arguments and thus build the images of the quota policy, therefore shaping understandings and viewpoints. This research will take into account the argumentative analysis, a theoretical aspect of Discourse Analysis taken from the works of Amossy (2010, 2011) and Lima (2006). In the context of ethnic and race relations, this paper will be focused mainly on the works of Munanga (2008) and Jesus (2011), starting from the biologizing perspective involving the concept of race and passing through the construction of national identity up until contemporary perspectives. We will also reflect upon the notion of discursive genre taken from Bakhtin (2006), together with the contributions of Semiolinguistics Theory from Patrick Charaudeau (2004) in relation to the social anchoring of genres. We assume that the arguments used by speakers have an argumentative purpose not just about quotas policies in higher education, but also about how race relations developed in Brazil and about the racism resulting from this process.